KEBIJAKAN HUKUM PIDANA TERHADAP PROSTITUSI ONLINE DI KALANGAN REMAJA PERSFEKTIF KEADILAN - Widhy Andrian Pratama; Sitti Khadijah Nurfajri; Gunawang Gunawang (Fakultas Hukum Universitas Wiraraja, 2026)
Online prostitution practices involve not only posting content on social media but also utilizing complex communication strategies to implicitly attract consumers. The inclusion of photos or videos of sex workers and the use of keywords such as